2021
DOI: 10.1210/clinem/dgab131
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience of the Efficacy and Safety of Low-dose Tolvaptan Therapy in a UK Tertiary Oncology Setting

Abstract: Background In patients with cancer, hyponatraemia is associated with increased morbidity and mortality and can delay systemic therapy. Methods The safety and efficacy of low-dose tolvaptan (7.5 mg) for hospitalized, adult patients with hyponatraemia due to Syndrome of Inappropriate Antidiuresis (SIAD), and co-existing malignancy were retrospectively evaluated in a tertiary cancer centre. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…The largest study to date of low-dose tolvaptan reported the outcomes of using a starting 7.5 mg tolvaptan dose in 55 patients with malignant SIAD and a mean baseline serum sodium of 117.9 mmol/litre. 36 After the initiation of tolvaptan, the median serum sodium increase was 9 and 10 mmol/litre at 24 and 72 h, respectively, with the vast majority of patients (87.3%) achieving a serum sodium rise of at least 5 mmol/litre over 48 h. However, the high efficacy of low-dose tolvaptan was accompanied by a high rate (30.9%) of overly rapid hyponatraemia correction. 36 Post-marketing assessments of tolvaptan use in Europe have reported that a significant proportion of physicians use a low 7.5 mg tolvaptan starting dose on a patient-by-patient case basis, with the hope of lowering the risk of overly rapid sodium correction.…”
Section: Efficacy and Safety Of Low Tolvaptan Dosesmentioning
confidence: 96%
See 2 more Smart Citations
“…The largest study to date of low-dose tolvaptan reported the outcomes of using a starting 7.5 mg tolvaptan dose in 55 patients with malignant SIAD and a mean baseline serum sodium of 117.9 mmol/litre. 36 After the initiation of tolvaptan, the median serum sodium increase was 9 and 10 mmol/litre at 24 and 72 h, respectively, with the vast majority of patients (87.3%) achieving a serum sodium rise of at least 5 mmol/litre over 48 h. However, the high efficacy of low-dose tolvaptan was accompanied by a high rate (30.9%) of overly rapid hyponatraemia correction. 36 Post-marketing assessments of tolvaptan use in Europe have reported that a significant proportion of physicians use a low 7.5 mg tolvaptan starting dose on a patient-by-patient case basis, with the hope of lowering the risk of overly rapid sodium correction.…”
Section: Efficacy and Safety Of Low Tolvaptan Dosesmentioning
confidence: 96%
“…36 After the initiation of tolvaptan, the median serum sodium increase was 9 and 10 mmol/litre at 24 and 72 h, respectively, with the vast majority of patients (87.3%) achieving a serum sodium rise of at least 5 mmol/litre over 48 h. However, the high efficacy of low-dose tolvaptan was accompanied by a high rate (30.9%) of overly rapid hyponatraemia correction. 36 Post-marketing assessments of tolvaptan use in Europe have reported that a significant proportion of physicians use a low 7.5 mg tolvaptan starting dose on a patient-by-patient case basis, with the hope of lowering the risk of overly rapid sodium correction. 37,38 All real-world studies suggest that a starting 7.5 mg dose, half the approved initiation dose of tolvaptan, is effective in treating hyponatraemia.…”
Section: Efficacy and Safety Of Low Tolvaptan Dosesmentioning
confidence: 96%
See 1 more Smart Citation
“…However, subsequent real world studies have reported much higher rates of overcorrection, 12.1–31%. 17 , 69 , 70 Overcorrection is a possibility with all effective therapies for hyponatraemia, and the key issues are awareness of the possibility, frequent monitoring of plasma sodium concentration in the 24 hours after initiation of therapy, and willingness to correct early with dextrose or dDAVP. Concurrent use of other hyponatraemia treatments should be avoided.…”
Section: Impact Of Treatment Of Hyponatraemia; Why Should We Treat It?mentioning
confidence: 99%
“… 69 , 71 A case series of 61 hospital inpatients by Tzoulis et al reported a significant negative correlation between baseline plasma sodium concentration and 24 hour sodium rise; 29% of patients with starting pNa <125 mmol/L exceeded the safe rate for pNa correction at any timepoint compared with none of those with pNa ⩾125 mmol/L. 69 , 71 Lower doses of tolvaptan (7.5 mg or less) are efficacious, 70 , 72 , 73 and may be safer, though it is important to stress that plasma sodium responses to lower doses of tolvaptan have not been subjected to rigorous prospective study.…”
Section: Impact Of Treatment Of Hyponatraemia; Why Should We Treat It?mentioning
confidence: 99%